Adsorption Properties of Ni(II) by D301R Anion Exchange Resin - Song Xiuling; Du Huipu; Liu Shijun; Qian Hui (Journal of Chemistry)
The adsorption of Ni(II) with D301R resin was investigated in this paper. The results showed that the saturated extent of adsorption Ni(II) by the resin was 84.3 mg/g. The equilibrium data of Ni(II) sorption was better described by Langmuir isotherm model (r2=0.994) while that of Ni(II) sorption also fitted in Freundlich isotherm model within the experimental concentration range. The amount of the constant (q0) of Ni(II) under 298 K in Langmuir model was 76.92 mg/g, which was close to the experimental results. The constant n was within 2–10 in Freundlich model; it was shown that adsorption of Ni(II) by the resin was easy to take place. The uptake kinetics followed the Lagergren pseudo-first-order rate equation (r2=0.9813). The particle diffusion controlled the adsorption process of Ni(II). The coefficient of the intraparticle diffusion increased with the increase of the pH values and the concentration of Ni(II) in aqueous solution. There was a drop of 20.1 cm−1 for the bending vibration frequency of N–H bond. Results showed that the adsorption of Ni(II) by D301R anion exchange resin was the surface complexation through the infrared spectrum analysis.